Rice productivity in Myanmar: Assessment of the 2021 monsoon and outlook for 2022 - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
We analyze rice input and productivity data for the monsoon seasons of 2020 and 2021 from the Myanmar Agriculture Performance Survey (MAPS). The survey covers plots of 2,672 rice producers, spread over 259 townships in all states/regions of the country. We find that: 1. Rice productivity at the national level during the monsoon of 2021 decreased on average by 2.1 percent compared to the monsoon of 2020. Considering estimated area reductions, national paddy production decreased by 3.4 percent compared to the monsoon of 2020. 2. Some areas performed substantially worse. Rice yields were low and declined significantly in Kayah and Chin, two conflict-affected states that have shown the highest levels of food insecurity in recent assessments. 3. Prices for most inputs used in rice cultivation increased significantly between these two seasons. Prices of urea, the most important chemical fertilizer used by rice farmers, increased by 56 percent on average and mechanization costs increased by 19 percent. 4. Paddy prices at the farm increased by 8 percent, significantly less than input prices, squeezing rice farmers’ profits during the monsoon of 2021. Despite the substantial hurdles in production and marketing due to the political crisis and international market developments, the results of the Myanmar Agricultural Performance Survey show the overall resilience of rice production during the monsoon of 2021. While the rice sector has been a source of stability in the country, the situation for future crop seasons is however concerning given further increases in input prices (especially fertilizer), the overall reduced profitability of rice farming, the reduced coping strategies remaining for rice farmers, and currency policy changes by the military government.